Listening to Interviews: Attending to Aurality, Emotions, and Atmospheres in Qualitative Analysis - Ashley Barnwell (Forum: Qualitative Social Research)
Sociologists commonly record interviews; however, most coding and analysis is done from transcriptions rather than from the audio recording itself. Transcribing sound into text is an often unquestioned and almost hallowed step in qualitative research. Yet, the question of what is lost in transcription is worth revisiting given advances in artificial intelligence, ethics, and new conceptual concerns that challenge processes of knowledge production. In this article, I aim to offer inspiration for listening to interviews—data that can be heard—in qualitative research. I discuss practical, ethical, and conceptual considerations that may come with analyzing interview recordings, tracking the reasons why scholars have come to rely on transcripts and the possible shortcomings of doing so. I argue that by adhering to a tradition of working with only the transcript, researchers miss rich layers of sensory, emotional, and embodied data. Instead, I suggest the use of listening as one of the key methods in analyzing the constitutive role of emotions and atmospheres in qualitative interview research.